Cuentas por pagar en la Empresa Royma S. A. del cantón Ventanas durante el periodo 2022 - 2023. - Castañeda Cisneros, Nayely Michelle (2024)
Accounts payable refer to all those debts that the company has contracted on credit to carry out its operations. The main objective of the research is to evaluate the accounts payable in the Company Royma S. A of the Ventanas canton during the period 2022 - 2023. The methodology implemented was a mixed approach, because qualitative analysis and research techniques are applied and quantitative. The scope is descriptive. The types of research were field and documentary; while, the method used is the inductive one. The techniques applied were two: interview and documentary review. The results of the investigation allowed us to conclude that: Accounts payable increased drastically from one period to another. In the year 2023, the amounts pending payment presented a positive variation of 210% compared to the immediately previous period. The scenario must be taken into account because it can condition the financial health of Royma S. A since the significant increase in debts in the short term can compromise current liquidity and the timely payment of financial obligations. Likewise, the turnover of accounts payable of Company Royma S. A during the 2022 period was 0.09 times; while in the period 2023 it increased slightly by 0.061 times.